Tree Water Use Patterns as Influenced by Phenology in a Dry Forest of Southern Ecuador - Butz, Philipp; Hölscher, Dirk; Cueva, Eduardo; Graefe, Sophie (Frontiers in Plant Science, 2018)
Tropical dry forests are composed of tree species with different drought coping strategies and encompass heterogeneous site conditions. Actual water use will be controlled by soil moisture availability. In a premontane dry forest of southern Ecuador, tree water use patterns of four tree species of different phenologies were studied along an elevational gradient, in which soil moisture availability increases with altitude. Main interest was the influence of variation in soil moisture, vapor pressure deficit, species (representing phenology), elevation and tree diameter on water use. Special emphasis was put on the stem succulent, deciduous Ceiba trichistandra, as high water use rates and drought coping involving stem succulence was to be expected. Tree water use rates increased linearly with diameter across species at high soil water content. However, when soil moisture declined, sap flux densities of the species responded differently. The stem succulent, deciduous Ceiba and other deciduous tree species reduced sap flux sensitively, whereas sap flux densities of the evergreen (broad leaved) Capparis scabrida were increasing. This was also reflected in diurnal hysteresis loops of sap flux vs. vapor pressure deficit (VPD) of the air. Under dry soil conditions Ceiba and other deciduous tree species had much smaller areas in the hysteresis loop, whereas the area of Capparis was largely enhanced compared to wet conditions. The evergreen Capparis potentially had access to deeper soil water resources as water use patterns suggest that top soil drought was tolerated. The deciduous species followed a drought avoidance strategy by being leafless in the dry season. The stem succulent deciduous Ceiba flushed leaves at the end of the dry season before the rainy season began and also re-flushed early in the dry season after a rain event; however water use rates at this occasion remained low. Ceiba was also ready for fast and strong response in water use when conditions were most favorable during the wet season. The study thus indicates a strong influence of species’ drought coping strategy on water use patterns in tropical dry forests.